159k views
5 votes
Find g(5) and f(g(5))

f(x)=x^2-x+2
g(x)=4x-3

g(5)=

f(g(5))=

2 Answers

1 vote

Answer:

g(5) = 17

f(g(5)) = 274

Explanation:

We are given the following two functions and we are to find the value of
g (5) and
f ( g (5) ):


f (x) = x^2 - x + 2


g (x) = 4x - 3

Finding
g (5) by substituting the given value 5 in it:


g (5) = 4(5) - 3 = 20 - 3 = 17

Now finding
f ( g (5) ):


f ( g (5) ) = x^2 - x + 2 = (17)^2 - (17) + 2 = 274

User Janay
by
5.0k points
3 votes

Answer:


g(5)=17


f(g(5))=274

Explanation:

1. First you must substitute x=5 into g(x), then you obtain:


g(x)=4x-3\\


g(5)=4*5-3


g(5)=17

2. Now, you must insert g(x) into f(x), as you can see below:


f(x)=x^(2)-x+2


f(g(x))=(4x-3)^(2)-(4x-3)+2

3. Finally, you must susbtitute x=5 into f(g(x)), as following:


f(g(5))=(4*5-3)^(2)-(4*5-3)+2


f(g(5))=274

User Adithya
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.